Efektivitas Osmopriming dalam Meningkatkan Vigor dan Viabilitas Benih Bayam - Adhitya Vishnu Pradana; Anung Wahyudi; Mertya Anugrah (Politeknik Negeri Lampung., 2025)
The availability of quality spinach (Amaranthus sp.) seeds is often hampered by expiration issues that drastically reduce germination. This study aims to analyze the effectiveness of osmopriming treatment in restoring the physiological quality of expired spinach seeds and determine the most optimal time for observing radicle emergence (ER). The experiment was conducted in April–May 2025 at the Seed Science Laboratory of Lampung State Polytechnic using a one-factor Completely Randomized Design (CRD). Spinach seeds that had expired for six years were given four invigoration treatments, namely Control, 5% KNO₃, 5% PEG 6000, and 150 ppm GA₃ with four replications. The results showed that osmopriming using 5% PEG 6000 and 150 ppm GA₃ was the best treatment in significantly increasing seed viability and vigor. The 5% PEG 6000 treatment produced the highest germination rate (98.66%) and the best vigor index (82.66%), followed by GA3150 ppm which produced the fastest growth rate of 96.02% KN/etmal. In contrast, the control treatment gave the lowest results with the percentage of abnormal shoots reaching 16.00%. Through the rapid test method, the 5% PEG 6000 and 150 ppm GA3 treatments were able to trigger the fastest radicle emergence with an extreme exponential curve spike since the 16th hour after imbibition. The most optimal RE observation time was achieved at the 30th hour by the 5% PEG 6000 treatment (97.33%) and reached a perfect accumulation of 100.00% at the 42nd hour by the 150 ppm GA3 treatment. This study proves that the RE test is effective as a rapid indicator to evaluate the recovery of vigor of small spinach seedlings.